Quantitative assessment of the degree of harmony between humanity and nature for national parks in China: A case study of the Three-River-Source National Park - Guo, Yanming; Liu, Xiaojie; Liu, Xiaohuang; Zhang, Jiahong; Zhang, Haiyan; Fan, Jiangwen; Khan, Nawab; Ma, Jiliang (Frontiers in Ecology and Evolution, 2023)
National parks, defined as the mainstay of the nature reserve system in China, pursue to achieve scientific protection and rational utilization of natural resources. However, eco-environmental benefit and socio-economic benefit are rarely considered together. Hereby, how to quantitatively express the relationship between humanity and nature in national parks needs further exploration. We selected the Three-River-Source National Park (TRSNP), which is China's largest area and the world's highest altitude national park, as a representative case to construct an evaluation model for the degree of harmony between humanity and nature of the national alpine ecological park. Based on the field survey data, meteorological data, remote sensing data and socio-economic data, the study used the model inversion and the spatial analysis method to quantitatively evaluate the degree of harmony consisting of twelve indexes from a fresh perspective in combination ecological environment with social economy. Namely to the TRSNP establishment in 2016 as the time node, we assessed and compared the degree of harmony between humanity and nature of the dynamic baseline period (2011-2015) and the evaluation period (2016-2020). The results show that the degree of harmony between humanity and nature showed a gradual upward trend from the northwest to the southeast in the TRSNP. Compared with the dynamic baseline period, the eco-environmental level and socio-economic level of the evaluation period increased in different degrees by 34.48% and 5.46%, respectively. Overall, the degree of harmony between humanity and nature visibly increased by 23.38%. This study developed a novel comprehensive method for evaluating national parks at regional scale to the win-win goal in both protection and development, and it provides theoretical basis for effective planning and management policies of national parks.